2018
DOI: 10.1097/aap.0000000000000824
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboid Intercostal and Subserratus Plane Block

Abstract: Our preliminary cadaveric and clinical data suggest that RISS block anesthetizes the lateral cutaneous branches of the thoracic intercostal nerves and can be used in multiple clinical settings for chest wall and upper abdominal analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 21 publications
0
72
0
Order By: Relevance
“…This fascia is continuous throughout the cervical, thoracic and lumbar spine,18 19 which facilitates injectate spread 6. This study provides evidence that the fascial plane in the thoracic area deep to ES muscles, the target for ESP block, is in continuity caudally with the MTLF in the lumbar region posterior to the QL muscle, medially superficial to the laminae for the retrolaminar block and laterally with the tissue plane deep to the rhomboid and serratus anterior muscles for the rhomboid intercostal and subserratus block 20. With current nomenclature, injection at any of these points along the same tissue plane may be considered different techniques based on needle insertion site despite continuity of planes.…”
Section: Discussionmentioning
confidence: 69%
“…This fascia is continuous throughout the cervical, thoracic and lumbar spine,18 19 which facilitates injectate spread 6. This study provides evidence that the fascial plane in the thoracic area deep to ES muscles, the target for ESP block, is in continuity caudally with the MTLF in the lumbar region posterior to the QL muscle, medially superficial to the laminae for the retrolaminar block and laterally with the tissue plane deep to the rhomboid and serratus anterior muscles for the rhomboid intercostal and subserratus block 20. With current nomenclature, injection at any of these points along the same tissue plane may be considered different techniques based on needle insertion site despite continuity of planes.…”
Section: Discussionmentioning
confidence: 69%
“…Initially, we identified 368 articles, out of which 233 articles were excluded because they were duplicates; however, 4 additional articles were identified from a different source and included in the review. Of the 139 remaining articles, 2 were excluded after reading the abstracts [126,127] which revealed that they were not related to ESP blocks. One was a review of adjuvant nerve blocks, and the other was an anatomical study of a different type of block.…”
Section: Methodsmentioning
confidence: 99%
“…This ''continuous plane'' has been shown by the newly described ''rhomboid intercostal and subserratus plane'' block. 4 In cadavers, the presence of rib fractures facilitated a deeper and more posterior spread of SP injections when compared with a hemithorax with intact ribs.…”
mentioning
confidence: 98%